Úlcera venosa: proposta educacional para enfermeiros da Atenção Primária à Saúde - Sousa, Alana Tamar Oliveira de (2015)
Introduction: Nurses from Primary Health Care (PHC) have faced difficulties to provide people with venous ulcer (VU) with care, due to poor knowledge on the theme. This research has emerged as an educational proposal for these professionals, based on the Theory of Meaningful Learning. Objective: Evaluate the effects of an educational intervention guided by the Theory of Meaningful Learning, as a strategy to change the theoretical and practical knowledge of nurses from PHC on care for a person with venous ulcer. Method: Quasi-experimental research, with a before-after design and a quanti-qualitative approach, carried out with 78 nurses who work in the Family Health centers (FHCs) in João Pessoa, Paraíba, Brazil. The inclusion criteria were: having within the area covered by the FHC a user with VU; having schedule availability to attend the course. The exclusion criteria were: missing the first or last day and having more than one absence during the educational intervention. The operational steps of the research were: (1) Preparation of the data collection instruments; (2) Validity and reliability of data collection instruments; (3) Diagnostic assessment; (4) Educational intervention; (5) Quantitative assessment; (6) Qualitative assessment. The educational intervention took place between April and June 2014, with a workload of 35 hours. Participants answered a self-assessment instrument and a questionnaire with items related to a person with VU, before and after the intervention. After six months, ten nurses were interviewed to constitute the qualitative analysis. In the analysis of quantitative data, we used the version 21.0 of the statistical package SPSS, with descriptive and inferential analyses and structural equations in the software AMOS Grafics, version 21.0. In the qualitative analysis, we used Bardin’s content analysis technique. The research was approved by the Research Ethics Committee, of the Health Sciences Center, under the Protocol 0708/13. Results: Most of the participants are women (95%), aged between 26 and 69 years, having an average education length of 18.6 years and an average of 12.7 years working with PHC. The self-assessment instrument proved to be reliable and it identified that the two-factor model is what best explains nursing care for a person with VU, understood through theory and practice. In self-assessment, there was an advance in scores between before and after that, on the assessment scale, came from average values close to no knowledge to mean scores closer to excellent, in almost all items. Besides, more than half of the participants hit the questions on VU assessment, prevention, and treatment, after the intervention, and there was a significant increase in the number of correct answers in relation to those stating “I do not know.” In qualitative analysis, the following categories emerged: Category I - Evaluating the training course; Category II - Barriers for applying the knowledge acquired; and Category III - Easy ways for applying content in daily work. Conclusion: The educational intervention for nurses from PHC, in the light of the Theory of Meaningful Learning, generated knowledge change regarding care for a person with VU. However, there is a need to keep the opportunity of Continued Health Education open for these professionals.